A phase 1b/2 study of azacitidine with PD‐L1 antibody avelumab in relapsed/refractory acute myeloid leukemia. Issue 20 (25th June 2021) - Saxena, Kapil; Herbrich, Shelley M.; Pemmaraju, Naveen; Kadia, Tapan M.; DiNardo, Courtney D.; Borthakur, Gautam; Pierce, Sherry A.; Jabbour, Elias; Wang, Sa A.; Bueso‐Ramos, Carlos; Loghavi, Sanam; Tang, Guillin; et al.
Abstract : Background: Patients with relapsed/refractory (R/R) acute myeloid leukemia (AML) have limited treatment options. In preclinical models of AML, inhibition of the PD‐1/PD‐L1 axis demonstrated antileukemic activity. Avelumab is an anti–PD‐L1 immune checkpoint inhibitor (ICI) approved in multiple solid tumors. The authors conducted a phase 1b/2 clinical trial to assess the safety and efficacy of azacitidine with avelumab in patients with R/R AML. Methods: Patients aged ≥18 years who had R/R AML received azacitidine 75 mg/m 2 on days 1 through 7 and avelumab on days 1 and 14 of 28‐day cycles. Results: Nineteen patients were treated. The median age was 66 years (range, 22‐83 years), 100% had European LeukemiaNet 2017 adverse‐risk disease, and 63% had prior exposure to a hypomethylating agent. Avelumab was dosed at 3 mg/kg for the first 7 patients and at 10 mg/kg for the subsequent 12 patients. The most common grade ≥3 treatment‐related adverse events were neutropenia and anemia in 2 patients each. Two patients experienced immune‐related adverse events of grade 2 and grade 3 pneumonitis, respectively. The overall complete remission rate was 10.5%, and both were complete remission with residual thrombocytopenia. The median overall survival was 4.8 months. Bone marrow blasts were analyzed for immune‐related markers by mass cytometry and demonstrated significantly higher expression of PD‐L2 compared with PD‐L1 both pretherapy and at all time points during therapy, with increasing PD‐L2 expression on therapy. Conclusions: Although the combination of azacitidine and avelumab was well tolerated, clinical activity was limited. High expression of PD‐L2 on bone marrow blasts may be an important mechanism of resistance to anti–PD‐L1 therapy in AML. Lay Summary: This report describes the results of a phase 1b/2 study of azacitidine with the anti–PD‐L1 immune checkpoint inhibitor avelumab for patients with relapsed/refractory acute myeloid leukemia (AML). The clinical activity of the combination therapy was modest, with an overall response rate of 10.5%. However, mass cytometry analysis revealed significantly higher expression of PD‐L2 compared with PD‐L1 on AML blasts from all patients who were analyzed at all time points. These data suggest a novel potential role for PD‐L2 as a means of AML immune escape. Abstract : Azacitidine combined with the anti–PD‐L1 immune checkpoint inhibitor avelumab does not produce significant clinical efficacy for patients with relapsed/refractory acute myeloid leukemia (AML). However, an analysis of AML blasts reveals PD‐L2 surface expression as a novel mechanism of immune escape.